Annealing behavior of Al-Mg-Mn alloy processed by ECAP at elevated temperature - 蒋大鸣 宁江利 孙俭峰 胡志敏 侯毅 (Transactions of Nonferrous Metals Society of China, 2008)
An Al-Mg-Mn alloy was subjected to equal channel angular pressing（ECAP） at 350 ℃ for 6 passes. Static annealing was conducted on the deformed alloy at various temperatures from 400 to 450 ℃ for lh respectively. The microstructural evolutions of both the deformed and the annealed materials were studied by electron back scattering diffraction pattern（EBSD） analysis. A fine-grained structure with （sub）grain size of about 2 μm is obtained after 6 ECAP passes, and the fraction of high-angle boundaries is 48.08%. As the annealing temperature increases, the average misorientations of the grain boundaries and the fraction of high-angle boundaries increases gradually. No grain growth takes place in the 400 ℃ annealed sample, while after annealing at 450 ℃ a coarse-grained structure replaces the initial fine-grained structure produced by ECAP. The aspect ratios remain almost constant and the （sub）grains keep equiaxed in the range of the present experiment. As the annealing temperature increases, the strength decreases obviously, which attributes to the relaxation of the internal stresses and the grain growth, while the elongation increases slightly.